2015
DOI: 10.1007/s11356-015-4607-3
|View full text |Cite
|
Sign up to set email alerts
|

The brown mussel Perna perna (L., 1758) as a sentinel species for chlorinated pesticide and dioxin-like compounds

Abstract: To contribute to the use of the tropical brown mussel Perna perna as a sentinel species for organochlorine pesticides (OCP) and polychlorinated biphenyls (PCB), the present study reports data on the toxicokinetics of these compounds in P. perna. Specifically, the authors present data on OCP and PCB bioaccumulation for eight sampling months from three bays (SE Brazil) and two transplant experiments (each 1 month long). Although seasonality is observed in the total lipid content of the whole soft tissue, with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…For Mali Ston Bay, the average contribution of DDE:DDD:DDT was 59.7%:24%:20.3% and 61%:20.1%:18.9% for 1-and 2-year-old mussels, respectively (Figure 5). The prevailed contribution of p,p -DDE is attributed to its high chemical stability, hydrophobia, long half-life, and persistence in abiotic and biotic aquatic compartments [35]. Similar findings were reported by Ramu et al [36], but a difference was found in mussels from Korea (29.6%:43%:27.5%) [37].…”
Section: Ocs-accumulation Patternsupporting
confidence: 72%
“…For Mali Ston Bay, the average contribution of DDE:DDD:DDT was 59.7%:24%:20.3% and 61%:20.1%:18.9% for 1-and 2-year-old mussels, respectively (Figure 5). The prevailed contribution of p,p -DDE is attributed to its high chemical stability, hydrophobia, long half-life, and persistence in abiotic and biotic aquatic compartments [35]. Similar findings were reported by Ramu et al [36], but a difference was found in mussels from Korea (29.6%:43%:27.5%) [37].…”
Section: Ocs-accumulation Patternsupporting
confidence: 72%
“…Brazil allowed the production of aldrin until 1990 and its use as wood preservative until 2000, while dieldrin has no register of use in Brazil but its production for export occurred until 1998occurred until (MMA, 2015Almeida et al, 2007). However, since aldrin and dieldrin have been reported in crabs (Souza et al, 2008) and in mussels (Galvão et al, 2015) from Southeastern Brazil, the occurrence of the emerging pollutant Dec 603 in whitemouth croaker in this region could be associated to the production and use of these pesticides.…”
Section: Pollutant Exposure Of Whitemouth Croakers From Southeastern mentioning
confidence: 99%
“…Therefore, they are extensively used as sentinels for chemical pollution monitoring in natural environments (Hellou and Law, 2003;OSPAR, 2016). Despite several studies showed that changes in environmental conditions (i. e. water temperature) or the annual reproductive cycle of mussels, may influence their response to chemical pollution (Costa et al, 2008;González-Fernández et al, 2016;Maulvault et al, 2016;Serra-Compte et al, 2018b) few studies considered seasonality when assessing bioconcentration of contaminants on these organisms (Claudi and Mackie, 1994;Costa et al, 2008;Galvao et al, 2015). On the other hand, the presence of antibiotics in marine mussels may pose a risk for consumers such as allergy and toxicity (Cabello, 2006).…”
Section: Introductionmentioning
confidence: 99%